Static mechanical performance of aluminum alloys 7075 and 2A12 for front uprights in racing formula cars - Xinqiao Ding; Lingyi Fang; Xia Liu (Advances in Mechanical Engineering)
The upright is a critical component of Formula cars. While traditional 7075 aluminum alloy uprights exhibit susceptibility to surface wear and corrosion potentially compromising stability, 2A12 aluminum alloy offers superior characteristics including low density, high specific strength, excellent wear/corrosion resistance, and enhanced machinability. Using CATIA, we developed 3D models of the front upright, analyzing the driving force, rolling resistance, and braking force. This study conducts a comparative mechanical analysis of 7075 and 2A12 aluminum alloy uprights under racing conditions. Results show peak stress and deformation occur during high-speed cornering, with 2A12 demonstrating superior performance (0.466 mm deformation, 265.38 MPa stress, 1.5687 kg mass) versus 7075 (0.479 mm, 265.54 MPa, 1.5711 kg). The 2A12 alloy exhibits 2.7% lower deformation and 0.15% mass reduction, providing measurable advantages for vehicle lightweighting and performance optimization.